Pronominal phrases in the French translation of Miguel Delibes' Cinco horas con Mario - Leví Caballero Artigas, Héctor (Romanica Olomucensia, 2023)
The typology of idioms has been the main topic of numerous works and, moreover, it is still a somewhat controversial subject. The present paper aims at analysing the French translation of the pronominal phrases that appear in the novel Cinco horas con Mario by Miguel Delibes. This work has been chosen because of its notable richness and value from the phraseological point of view. The corpus of this paper is composed of 16 pronominal phrases. Its focus is on the study of these idioms and on their translations in the two French editions of the novel. After the analysis of idioms of this type in Delibes' novel, it has been observed that the most commonly-used technique is phraseological correlation; in other words, generally, idioms have been translated by means of another idiom in the target language. This is interesting because of the great pragmatic value of idioms of this type. The lack of consensus on the consideration of pronominal phrases as a class apart from nominal phrases means that there is no common and precise cataloguing of these units in dictionaries and other lexicographic repertoires. On the other hand, here it is considered that this methodology is useful for the analysis and evaluation of the French translation of these constructions.
Keywords: phraseology; pronominal phrase; Cinco horas con Mario; translation